Pengaruh Corporate Social Responsibility, Profitabilitas Dan Leverage Terhadap Kinerja Keuangan (Studi Pada Perusahaan Property And Real Estate Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2019) - Ifa Nungki Safitri; Agus Widarko; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstrackThe purpose of this study was to determine the effect of corporate social responsibility, profitability and leverage on simultaneously and partially on financial performance in property and real estate companies listed on the Indonesia Stock Exchange in the 2016-2019 period, using purposive sampling method with data from 61 samples. to 26 because there were 35 samples that did not meet the sample selection criteria. This type of research is explanatory research. The method used in this research is multiple linear regression method.The results of this study indicate that Corporate social responsibility (CSR), profitability (ROA) and Leverage (DER) simultaneously have a significant effect on financial performance. And partially Corporate social responsibility (CSR) has no significant effect on financial performance, while Profitability (ROA) and leverage (DER) have a significant effect on financial performance. Keywords: Financial Performance, Corporate social responsibility, profitability, leverage.